Does a maternal history of abuse before pregnancy affect pregnancy outcomes? A systematic review with meta-analysis - Maryam Nesari; Joanne K Olson; Ben Vandermeer; Linda Slater; David M Olson (BMC Pregnancy and Childbirth, 2018)
Abstract Background Evidence relating maternal history of abuse before pregnancy with pregnancy outcomes is controversial. This study aims to examine the association between maternal histories of abuse before pregnancy and the risk of preterm delivery and low birth weight. Methods We searched Subject Headings and keywords for exposure and the outcomes through MEDLINE, EMBASE, Cochrane Database of Systematic Reviews, Cochrane Central Register of Controlled Trials, Psycinfo, CINAHL, Scopus, PILOTS, ProQuest Dissertations & Theses Global and Web of Science Core Collection in April 2017. We selected original studies that reported associations between maternal histories of abuse of any type and either preterm delivery or low birth weight. Studies that included interventions during pregnancy to lower maternal stress but reported no control data were excluded. We utilized the Newcastle-Ottawa Quality Assessment Scales for observational studies to assess the risk of bias in the primary studies. Two independent reviewers performed the selection of pertinent studies, assessment of risk of bias, and data extraction. Unadjusted pooled odds ratios (OR) with 95% Confidence Interval (CI) were calculated for the two outcomes of preterm delivery and low birth weight in 16 included studies. Results Maternal history of abuse before pregnancy was significantly associated with preterm delivery (OR 1.28, 95% CI: 1.12–1.47) and low birth weight (OR 1.35, 95% CI: 1.14–1.59). A substantial level of heterogeneity was detected within the two groups of studies reporting preterm birth and low birth weight (I2 = 75% and 69% respectively). Subgroup analysis based on the specific time of abuse before pregnancy indicated that childhood abuse increases the risk of low birth weight by 57% (95% CI: 0.99–2.49). When the included studies were categorized based on study design, cohort studies showed the highest effect estimates on preterm delivery and low birth weight (OR: 1.69, 95%CI: 1.19–2.40, OR: 1.56, 95% CI: 1.06–2.3, respectively). Conclusions We recommend that more high quality research studies on this topic are necessary to strengthen the inference. At the practice level, we suggest more attention in detecting maternal history of abuse before pregnancy during antenatal visits and using this information to inform risk assessment for adverse pregnancy outcomes. Trial registration Registration number: PROSPERO (CRD42016033231).